Diagnostics of early precancerous condition and breast cancer - Ruhland, Frank; Przybylski, Marcin; Budner, Marek; Spaczyński, Marek (Contemporary Oncology/Współczesna Onkologia, 2002)
Problem: Evaluation of the diagnostic value of mammography and sonomammography in impalpable breast lesions and the value of both methods in pre and intra surgical diagnostic procedures (breast lesion marking process, mammography and somomammography of tissue samples from surgery, high speed biopsy). Material and methods: From 16th of June 1995 up to 11th of August 1997 199 patient aged 29 to 85 years (mean age 53.6 years) underwent breast surgery. In each case, no palpable lesion was detected though suspicion had been raised by visualization diagnostic methods. Visualizing diagnostic methods were evaluated by calculating their sensitivity, specificty and both positive and negative predictive value on base of tissue histopatological results. Results: 33 invasive carcinomas, 6 ductal carcinomas "in situ" and 160 benign breast tumors were confirmed by histopatological examination. 28 cases (84.8%) of invasive breast cancer were diagnosed by mammography, 26 of which were confirmed by sonomammography. Two invasive breast cancers diagnosed by mammography only, were early invasive breast cancer stage pT1a (invasive ductal cancer of mammal duct) and stage pT1b (invasive cancer of mammal duct). 5 cases of breast cancer (15.2%) were diagnosed by sonomammography, while only one was confirmed by mammography. Breast cancer was diagnosed by sonomammography in 3 premenopausal and one postmenopausal women. Sensitivity of mammography and sonomammography was 87%. Combination of both methods led to the correct diagnosis at all impalpable breast cancers (sensitivity 100%). The specifity of mammography was 40% while that of sonomammography was 29%. The combination of both methods gave a specifity of 9%. All 15 invasive lesions marked with a hook under sonomammographical control were totally removed. Under mammography control only 19 from 24 preinvasive and invasive lesions were fully excised. Conclusion: Mammography dominates among diagnostic methods for impalpable focal breast lesions. It was found that pathological processes diagnosed by mammography are often confirmed by sonomammography. Additional use of sonomammography increased sensitivity especially in the group of premenopausal women and in so-called radiologically dense breast. In addition, such an approach makes pre and intra surgical management easier. Combination of both visualizing methods has negative influence on specificity, which is why additional high-speed biopsies should be performed in the future.